Effect of ora-pro-nobis (Pereskia aculeata Miller) improved oxidative stability of sausage - Henck, Jenifer Mayara Monari [UNESP]; Marquezini, Miriam Gonçalves; Echegaray, Noemí; Lorenzo, José Manuel; Silva Barretto, Andrea Carla [UNESP] (Oxford University Press (OUP), 2025)
ABSTRACT Unconventional food plants have been widely studied because their leaves are rich in phenolic compounds, making them of great interest to the food and pharmaceutical industries. This study aimed to evaluate the effects of adding freeze-dried ora-pro-nobis (OPN) leaves to sausages on lipid oxidation and physicochemical attributes during refrigerated storage, and to compare them with other natural commercial antioxidants (rosemary and green tea extracts) and a synthetic antioxidant (sodium erythorbate). Five treatments were prepared: a control without antioxidants (CON); 0.05 g/kg sodium erythorbate (ERY); 0.05 g/kg freeze-dried OPN leaves; 0.05 g/kg rosemary extract (ROS); and 0.05 g/kg green tea extract (GT). The ΔE* analysis showed that OPN and ROS were more effective in maintaining color stability of sausages during storage compared to GT and ERY, which exhibited greater color variation. After 60 days, OPN showed the lowest TBARS values (0.134 mg of MDA/kg sample), compared to CON (0.256 mg of MDA/kg sample) and ERY (0.196 mg of MDA/kg sample), indicating a greater inhibition of lipid oxidation, likely due to its high content of phenolic compounds and carotenoids, known for their radical scavenging. Induction time measured by RapidOxy was higher for ROS (67.80 min), GT (67.27 min), and OPN (52.94 min) than for CON (40.69 min) and ERY (40.33 min); that reflects greater oxidative stability and resistance to lipid degradation under accelerated oxidation conditions. Overall, ora-pro-nobis demonstrated promising potential as a natural antioxidant ingredient capable of enhancing color stability and reducing lipid oxidation in sausages, aligning with the growing consumer demand for clean-label and plant-based formulations.